Pelestarian Gapura Wringin Lawang Sebagai Potensi Sarana Edukasi di Trowulan - Yanda Bara Kusuma; Lugas Nugraha Nadra; Duta Rahma Safira; Marissa Ariny (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research focuses on the preservation of the Wringin Lawang Gate, a cultural heritage site in Trowulan, Mojokerto, which has historical value as a relic of the Majapahit Kingdom. A descriptive qualitative approach is used to evaluate the physical condition, accessibility, community participation, and educational potential contained in this site. The findings show that although the arch structure is still sturdy, there is damage to certain parts due to age and weather factors. Access to this site is quite good, but the supporting facilities are still limited. Educational activities at the Wringin Lawang Gate are still not optimal and require the development of a more structured program. The participation of local communities in site preservation already exists, but needs to be increased through active involvement in education and conservation activities. Recommendations for site managers include improving educational programs through modern technology such as augmented reality, as well as the development of supporting facilities to maximize the potential of the Wringin Lawang Gate as an effective and sustainable educational facility.